Hubungan kadar serum gamma-glutamyl transferase dengan profil lipid pada Diabetes Melitus-Tipe 2 (DM-2) terkontrol dan tidak terkontrol di Rumah Sakit Umum Pusat Haji, Adam Malik Medan, Indonesia - Furiyani Furiyani; Santi Syafril; Burhanuddin Nst (Intisari Sains Medis, 2019)
Background: Diabetes mellitus is a group of metabolic diseases with characteristics of hyperglycemia that occur due to impaired insulin secretion, insulin work, or both whereas also impaired lipid peroxidation caused by oxidative stress. Gamma-glutamyl transferase (GGT) is an enzyme on the surface of the cell membrane that is responsible for the catabolism of glutathione which acts as a marker of oxidative stress. This study aims to determine the relationship of serum GGT levels with lipid profiles in controlled and uncontrolled type 2 DM.Method: A cross-sectional study was conducted at H. Adam Malik General Hospital Medan from September - November 2018 among 60 patients with type 2 DM grouped according to HbA1c <7% controlled and HbA1C > 7% uncontrolled. GGT levels and lipid profiles examined using enzymatic calorimetry and HbA1c with Immunoturbidimetry method. The relationship of serum GGT levels with lipid profiles in controlled DM-2 was tested using the Pearson correlation test whereas controlled DM-2 correlation test using the Spearman's correlation test using SPSS version 21 for Windows.Results: Most of respondents were males with HbA1C levels <7% (53.3%) and HbA1C â‰¥ 7% (60.0%). There was no difference in the mean age and serum GGT levels between uncontrolled DM-2 or controlled DM-2 group (P = 0.260 and P = 0.520, respectively). There was no association between serum GGT levels and lipid profiles in the controlled type 2 DM group and uncontrolled type 2 DM. (r=P> 0.05).Conclusion: There is no significant relationship between serum GGT levels and lipid profiles in controlled and uncontrolled type 2 DM groups.